Reformulating Public Service Missions within the Digital Switchover: new Content and Citizen Uses of Digital Terrestrial Television in Global Society - Peinado y Miguel, Fernando; Rodríguez Barba, Dolores; Gutiérrez David, Estrella (Derecom. Revista Internacional de Derecho de la Comunicación y de las Nuevas Tecnologías, 2024)
Digital Terrestrial Television has been of the last platforms to establish itself in a market that already comprised Satellite TV, Cable, IPTV, ADSL, Mobile TV and High Definition TV. Spanish audiovisual market has just completed the analogue switch-off, whereas lawmaker has been introducing decisive changes in order to liberalize the audiovisual market while preparing the digitization. Spanish audiovisual has been immersed in a quite confused period in which the allocation of digital channels and multiplexes to public and private broadcasters has passed over a transitional period plenty of uncertainties about the future audiovisual business and in which the public service broadcasting model is being questioned by lawmaker. This market is considered to offer a broad audience for content that may be different, public service oriented or simply commercial free or fee based, targeted at proximity or global market. A variety of content will be disseminated to a multitude of consumers, whose traditional passive role will change into an active one that seeks information, public services and entertainment. Much more, if new technologies enable consumers, they may also be generators of digital products by participating in the Society of Information and Knowledge. With the advent of DTT, both interactivity and high definition are fundamental values to develop new content and new citizen uses that might force the lawmaker to reformulate the public service broadcasting within the T-services.